Iron man 3 - Bridges, Jeff, 1949-; Cheadle, Don; Downey, Robert, Jr., 1965-; Favreau, Jon; Hall, Rebecca, 1982-; Howard, Terrence; Jackson, Samuel L.; Johansson, Scarlett, 1984-; Kingsley, Ben, 1943-; Paltrow, Gwyneth, 1972-; Pearce, Guy, 1967-; Rockwell, Sam; et al. (Avusturya : Tiglon, 2013)
"When Tony Stark/Iron Man finds his entire world reduced to rubble, he must use all his ingenuity to survive, destroy his enemy, and somehow protect those he loves. But a soul-searching question haunts him: Does the man make the suit-- or does the suit make the man?"--Container.
Title from container.
Bonus : Marvel one-shot: agent carter; Marvel's Iron Man 3 unmasked; Deconstructing the scene: attack on Air Force One ; deleted & extended scenes; Gag reel; Exclusive behind-the-scenes look - Marvel's thor: the dark world; Commentary by Shane B lack and Drew Pearce.
Originally released as a motion picture in 2013.
Directors, Shane Black, Jon Favreau; producers, Avi Arad, Kevin Feige.
Jeff Bridges, Don Cheadle, Robert Downey Jr., Jon Favreau, Rebecca Hall, Terrence Howard, Samuel L. Jackson, Scarlett Johansson, Ben Kingsley, Gwyneth Paltrow, Guy Pearce, Sam Rockwell, Mickey Rourke.
Genel izleyici kitlesi içindir.
Keywords: Iron Man (Fictitious character); Terrorists -- Drama; Good and evil